Nuciferine induces autophagy to relieve vascular cell adhesion molecule 1 activation via repressing the Akt/mTOR/AP1 signal pathway in the vascular endothelium - Wei, Haibin; Yin, Yujie; Yang, Wenwen; Zhu, Jinyan; Chen, Lin; Guo, Rui; Yang, Zhen; Li, Songtao (Frontiers in Pharmacology, 2023)
Pro-inflammatory factor-associated vascular cell adhesion molecule 1 (VCAM1) activation initiates cardiovascular events. This study aimed to explore the protective role of nuciferine on TNFα-induced VCAM1 activation. Nuciferine was administrated to both high-fat diet (HFD)-fed mice and TNFαexposed human vascular endothelial cell line. VCAM1 expression and further potential mechanism(s) were explored. Our data revealed that nuciferine intervention alleviated VCAM1 activation in response to both HFD and TNFα exposure, and this protective effect was closely associated with autophagy activation, since inhibiting autophagy by either genetic or pharmaceutical approaches blocked the beneficial role of nuciferine. Mechanistical studies revealed that Akt/mTOR inhibition, rather than AMPK, SIRT1 and p38 signal pathways, contributed to nuciferine-activated autophagy, which further ameliorated TNFα-induced VACM1 via repressing AP1 activation, independent from transcriptional regulation by IRF1, p65, SP1, and GATA6. Collectively, our data uncovered a novel biological function for nuciferine in protecting VCAM1 activation, implying its potential application in improving cardiovascular events.